التعزيزات التربوية والمعرفية واللسانية والسياسية العقلانية، سبيل الأمازيغية إلى الترسيم وتحقيق المواطنة اللغوية - سعداني, الأخضر (University of El-oued, 2020)
الملخص: تطرح مقالتي جملة من الجوانب المتعلقة بتهيئة اللغة الأمازيغية في الجزائر. وهي تهيئة ذات أبعاد نفسية وتنظيمية وسياسية ولغوية. وهي في مجملها تقتضي عامل الزمن والانتظار والمثابرة. ولا مجال للقول بالتعجل في ترسيم الأمازيغية بالمعنى الذي يقول:"إنها قد أينعت وحان قطافها". مشروع الأمازيغية في الجزائر المعاصرة، منه ما هو بعث للثقافة الأمازيغية واستمرار في النضال لأجل إحيائها. ومنه ما هو نشرها واعتبارها لغة وطنية. ومنه ما هو مرادف للحركة البربرية، يروم الانسلاخ من صفتي العروبة والإسلام بكل الأشكال، ويعمل على القول بامتلاك تاريخ وعرق مميزين، يفصلانه عن الهوية العربية الإسلامية، متنكرا لأربعة عشر قرنا من انتماء أصوله إلى سكان شمال أفريقيا الذين كانوا أمازيغ عربهم الإسلام، وافتخروا بذلك، وصنعوا التاريخ تحت عنوان الهوية العربية الإسلامية. أما الشق الثقافي فهو ينشط من حيث اعتباره مشروعا وطنيا، يأخذ مشروعيته من قرار الرئيس، ودسترته في الدستور، وتحت رعاية نخبة من الجزائريين المتخصصين، وغيرهم من النشطاء في سبيل تنمية وترقية وتوحيد الأمازيغية. الكلمات المفتاحية: معيرة اللغة; تهيئة اللغة الأمازيغية; اللغة المعيارية; الهوية; التخطيط اللغوي. Abstract : My article is to follow a number of aspects of multidimensional, psychological, organizational, political and linguistic preparations, in contemporary Algeria. The Tamazight project is multifaceted . From this is what is sent to Amazigh culture and the continuation of the struggle for revival, dissemination and take into consideration as a national language. And from the same project what is synonymous with the barbaric movement which wants to disengage from the class of Arabism and Islam in all forms . And works to say that having a distinctive history and race, separating himself from the Arab Islamic identity arabized by Islam, and his ancestors were proud of it. They made history under the banner of Arab Islamic identity. The cultural aspect is active in terms of being considered as a national project, taking its legitimacy from the President's decision, and constitutionalized in the Constitution under the auspices of a group of Algerian specialists, and other activists in the development, promotion and unification of Amazigh. It is a project that requires hard work, patience, honesty and good will. It also requires the recall of Algerian parties that make the decision as well.
مقال. Ex Professo. مج5. ع.1. جامعة الوادي
Keywords: الكلمات المفتاحية : معير اللغة; هيئة اللغة األمازيغية; اللغة املعيايية; الهوية; التوطيت اللغوي; key words :Standardization of language ; Creating the Amazigh language;Standard Language;Identity; Linguistic Planning.